Investigation and Study of High Voltage Capacitor Bank Techniques for Voltage Drop Improvement in 22-kV Distribution Line - Surakit Thongsuk; Praikanok Lertwanitrot; Panapong Songsukthawan; Santipont Ananwattanaporn; Atthapol Ngaopitakkul; Suntiti Yoomak; Chaichan Pothisarn (IEEE Access, 2025)
Voltage drop in distribution lines contributes to power losses, leading to a decrease in the overall efficiency of the electrical power system. In this paper, we investigate methods to improve voltage drop through capacitor bank allocation techniques, specifically installation at the end of the distribution line, the 1/2-kvar rule, and the 2/3-kvar rule. In the case study, a 22 kV overhead distribution line in Thailand is utilized as a model to analyze voltage drop improvement. The study is conducted using PSCAD software to simulate and evaluate the effectiveness of various capacitor bank allocation techniques in enhancing voltage drop in the distribution line. In addition, the impact of capacitor bank placement and sizing on voltage drop mitigation in a distribution line is analyzed through a proposed mathematical framework. This analysis considers the interaction between reactive current compensation and impedance of a distribution line, ensuring an optimized approach for capacitor bank deployment to enhance voltage drop. The results emphasize that the capacitor bank installation at the end of the distribution line yields the most substantial voltage drop improvement. This is attributed to the utilization of larger capacitor bank capacities compared to the 1/2-kvar and 2/3-kvar methods. Furthermore, the mathematical analysis confirms that both the placement and sizing of capacitor banks play a crucial role in voltage drop mitigation.
Keywords: Power Systems and Technologies; Vehicle License Plate Recognition; Power Systems and Renewable Energy